Indicators of the quality of general practice care of patients with chronic illness: a step towards the real involvement of patients in the assessment of the quality of care. Issue 2 (June 1996) - Wensing, M; Grol, R; van Montfort, P; Smits, A
Abstract : OBJECTIVE–To develop a list of indicators of the general practice care of people with chronic illnesses considered important by both patients and practitioners and to identify the indicators that are considered relevant for patient assessment of health care quality. DESIGN–Qualitative study with focus group interviews and a written consensus procedure. SETTING–General practice in the Netherlands in 1993. SUBJECTS–34 patients with chronic illness, mostly members of patient organisations, and 19 general practitioners with expertise in either chronic disease management or experience with patient surveys. MAIN MEASURES–Aspects of general practice care considered important for the delivery of good quality care that emerged from focus group interviews; the relevance of evaluations of 41 aspects of care for patients explored through the written consensus procedure. Those aspects of general practice care agreed to be both important and relevant by patients and general practitioners were considered to be suitable indicators for patient assessment of the quality of care. RESULTS–Patients and general practitioners differed to some extent in their assessment of the aspects of care that they considered important for quality. They agreed that most indicators of care that related to the ¿doctor-patient relation¿ and to ¿information and support¿ were relevant and therefore suitable as indicators for patient assessment of health care quality. There was less agreement about the relevance of indicators of ¿medical and technical care, ¿ ¿availability and accessibility, ¿ and ¿organisation of services.¿ CONCLUSIONS–Several indicators of the quality of general practice care of patients with chronic illness were thought to be suitable for the patient assessment of healthcare quality, but other indicators were not, mainly because of reservations by general practitioners. IMPLICATIONS– Qualitative methods can contribute to the selection of indicators for assessment of the quality of health care in areas where scientific evidence is limited or where patients' and providers' preferences are particularly important.